Chia (Salvia hispanica L.) as a novel forage and feed source: A review - Jamshidi, Amir M.; Amato, Mariana; Ahmadi, Ali; Bochicchio, Rocco; Rossi, Roberta (Italian Journal of Agronomy, 2019)
Chia (Salvia hispanica L.), is a traditional pre-Colombian food crop from Central America. Being considered the richest botanical source of omega-3 fatty acids, it has recently been rediscovered as a functional food and feed. A growing body of literature indicates that dietary chia seeds greatly improve animal products quality without compromising growth, productivity and organoleptic quality. Chia is mainly cultivated as a seed crop but recently interest has been raised on biomass production as a potential forage source opening alleys toward the integration of chia in crop-livestock systems. Literature on chia is flourishing, up to now reviews addressed botany, agronomy phytochemical and medicinal uses, this article reviews the main findings on chia use in animal nutrition and includes an overview on both seed and biomass yield and quality as affected by environment, agronomy, and genetic background. Chia is a short-day flowering crop, seed yields of commercial varieties can be as high as 2999 kg ha–1 in areas of origin while at European latitudes seed production is severely hampered by photoperiod sensitivity (max 518 kg ha–1). The viable growing of chia for seeds worldwide relies on the availability of genotypes flowering at longer days than in the areas of origin, while for whole plant a relatively high forage yield can be expected. In southern Italy commercial short-day flowering varieties yielded up to 2.07 t ha–1 of leaf dry biomass and in Greece chia yielded up to 15 T ha−1 dry biomass. Chia seeds supplement in livestock diet are administered with the main objective to increase the content of omega-3 and improve animal health. The majority of work has been done on poultry and rabbits where rewarding results have been obtained in terms of improvement of products lipids profile. Only one work was published on pig but the first results are encouraging. Published data on ruminants are few but in agreement with findings on other species these works demonstrate chia has no adverse effects health performances, and sizeable improvement of milk fatty acid profile. A qualitative improvement of freshwater cultivated fish fillets was also obtained with a partial replacement of soybean oil with chia. Finally an innovative study tested the effect of total or partial replacement of wheat bran in the diets of two edible insects that can be considered the new frontier of food and feed production chains.